2006
DOI: 10.4049/jimmunol.177.1.84
|View full text |Cite
|
Sign up to set email alerts
|

IL-2 Immunotoxin Therapy Modulates Tumor-Associated Regulatory T Cells and Leads to Lasting Immune-Mediated Rejection of Breast Cancers in neu-Transgenic Mice

Abstract: Studies in cancer patients have suggested that breast tumors recruit regulatory T cells (Tregs) into the tumor microenvironment. The extent to which local Tregs suppress antitumor immunity in breast cancer is unknown. We questioned whether inhibiting systemic Tregs with an IL-2 immunotoxin in a model of neu-mediated breast cancer, the neu-transgenic mouse, could impact disease progression and survival. As in human breast cancer, cancers that develop in these mice attract Tregs into the tumor microenvironment t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
98
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(107 citation statements)
references
References 43 publications
7
98
0
2
Order By: Relevance
“…Whether CLL cells can actively induce T regs or whether disease progression in CLL is only a consequence of the given immunologic constitution of a patient cannot be answered by our study. With T regdepleting and T reg -increasing substances in hand, [28][29][30][31] we have the means to test this hypothesis in preclinical tumor models, such as the Tcl1-mouse model for CLL. 32,33 …”
Section: Discussionmentioning
confidence: 99%
“…Whether CLL cells can actively induce T regs or whether disease progression in CLL is only a consequence of the given immunologic constitution of a patient cannot be answered by our study. With T regdepleting and T reg -increasing substances in hand, [28][29][30][31] we have the means to test this hypothesis in preclinical tumor models, such as the Tcl1-mouse model for CLL. 32,33 …”
Section: Discussionmentioning
confidence: 99%
“…A recent report supported this idea by demonstrating that denileukin diftitox-reduced T reg numbers, and overall suppression mediated by the CD4 þ CD25 þ cell population in a mouse model of breast cancer, with improved immunity and tumor regression. 38 The therapeutic effects of Ontak have also been investigated in a variety of neoplasms, including cutaneous T-cell leukemia/ lymphoma, 39 ovarian, breast, and pancreatic carcinomas. 40 Similarly, antibodies against T regs have been used in the management of malignant melanomas with promising results.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, our previous study demonstrated that Treg cell depletion, treated by a low dose of cyclophosphamide, potentiated the antitumor effect of immunization with an injection of immature dendritic cells into irradiated tumors (31). As well as in breast cancer, Treg cells were increased in the peripheral blood and greatly increased in the tumor microenvironment (32); the presence of Treg cells is likely to correlate with cancer progression (33), and specific depletion of Treg cells markedly inhibits tumor growth and maintains a strong and persistent antitumor immune response (34).…”
Section: Discussionmentioning
confidence: 99%